2013
DOI: 10.1111/ajt.12168
|View full text |Cite
|
Sign up to set email alerts
|

Antiperlecan Antibodies Are Novel Accelerators of Immune-Mediated Vascular Injury

Abstract: Acute vascular rejection (AVR) is characterized by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
149
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(151 citation statements)
references
References 27 publications
2
149
0
Order By: Relevance
“…In addition, its highest predictive value was increased in combination with other biomarkers, but they were not identical in the 2 replication sets. Its association was highest in replication set 1 with anti-LG3, a vascular rejection biomarker in kidney transplantation, 12,13 and in replication set 2, with CXCL9 and CXCR3 1 regulatory NK (NK reg ) cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, its highest predictive value was increased in combination with other biomarkers, but they were not identical in the 2 replication sets. Its association was highest in replication set 1 with anti-LG3, a vascular rejection biomarker in kidney transplantation, 12,13 and in replication set 2, with CXCL9 and CXCR3 1 regulatory NK (NK reg ) cells.…”
Section: Discussionmentioning
confidence: 99%
“…12 Anti-LG3 titers were measured with previously described laboratory-made enzyme-linked immunosorbent assay (ELISA). 13 Briefly, recombinant mouse LG-3 (10 mg/mL) was first coated on 96-well Nunc MaxiSorp plates (Thermo Scientific, Rochester, NY) for a total of 1 mg per well.…”
Section: Anti-perlecan Auto-antibodies (Anti-lg-3)mentioning
confidence: 99%
“…Additional studies support a contribution of non-HLA antibodies to pre-sensitization (7,13). More specifically, serum IgG reactivity to autoantigens such as cardiac myosin, vimentin, collagen, oxidized lipids and LG3 has been associated with increased rejection rates and reduced graft survival (14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 90%
“…As graft loss in this study could not be the result of anti-HLA alloreactivity, these data suggest an important role for immunity against antigens other than HLA in kidney transplantation. A substantial number of non-HLA antigens have been identified as targets of autoantibodies in kidney transplantation including vimentin, tubulin, myosin, collagen V, angiotensin type 1 receptor (AT1r), agrin, and LG3 [12][13][14][15][16][17][18][19]. The presence of antibodies against the glomerular basement membrane protein agrin was found in 11 of 16 patients with chronic transplant glomerulopathy and 3 of 6 controls with chronic allograft nephropathy in absence of chronic transplant glomerulopathy.…”
Section: Non-hla Antibodiesmentioning
confidence: 99%
“…In addition, in multiple studies autoantibodies against non-HLA antigens have been found in sera from patients on the waiting list for kidney transplantation. Depending on their specificity the presence of these antibodies has been associated with chronic transplant glomerulopathy, a higher number of acute rejection episodes, acute vascular rejection, refractory acute vascular rejection and malignant hypertension [10][11][12][13][14][15][16][17][18][19]. These data indicate that detection of preformed non-HLA antibodies may be useful in identifying patients at risk for graft loss.…”
Section: Introductionmentioning
confidence: 99%